2000
DOI: 10.1144/pygs.53.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A palynological investigation of the Lower and lowermost Middle Jurassic strata (Sinemurian to Aalenian) from North Yorkshire, UK

Abstract: SUMMARY A palynological investigation of the Lower and lowermost Middle Jurassic (Sinemurian to Aalenian) strata of North Yorkshire has been undertaken which incorporates material from the BGS Brown Moor Borehole, near Acklam and the coastal outcrops between Staithes and Robin Hood’s Bay. The resulting dataset is an additional contribution to the Jurassic dinoflagellate cyst biostratigraphy of northern England. Two distinctive variants of Liasidium variabile appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…In the present palynological study no dinoflagellate cysts at all have been found. This is in agreement with a previous study on the organic microplankton from the Sinemurian -Pliensbachian of Yorkshire by Bucefalo Palliani and Riding (2000), who analysed spot samples from Robin Hood's Bay and came to the same results. Their two samples from the siliceous shale (Raricostatum Zone) at Robin Hood's Bay were barren of dinoflagellate cysts, as well as the one sample from the Lower Pliensbachian (Davoei Zone) from the neighbouring Cowbar Nab section.…”
Section: Figure 6 Detail Of the Sinemurian-pliensbachian Boundary Insupporting
confidence: 92%
See 1 more Smart Citation
“…In the present palynological study no dinoflagellate cysts at all have been found. This is in agreement with a previous study on the organic microplankton from the Sinemurian -Pliensbachian of Yorkshire by Bucefalo Palliani and Riding (2000), who analysed spot samples from Robin Hood's Bay and came to the same results. Their two samples from the siliceous shale (Raricostatum Zone) at Robin Hood's Bay were barren of dinoflagellate cysts, as well as the one sample from the Lower Pliensbachian (Davoei Zone) from the neighbouring Cowbar Nab section.…”
Section: Figure 6 Detail Of the Sinemurian-pliensbachian Boundary Insupporting
confidence: 92%
“…A critical review of the pertinent literature seems to confirm the range top of L. variabile in the Late Sinemurian Oxynotum Zone to be a reliable stratigraphical marker datum (Feist-Burkhardt, ongoing study). Similar results, with productive samples from Oxynotum Zone and barren samples from Raricostatum and earliest Jamesoni Zones, were also reported from the Brown Moor borehole, some 50 km away from Robin Hood's Bay (Bucefalo Palliani and Riding, 2000).…”
Section: Figure 6 Detail Of the Sinemurian-pliensbachian Boundary Insupporting
confidence: 85%
“…Location and geological setting of Hasty Bank, northeast England. Modified from Milsom and Rawson (1989); Mjøs and Prestholm (1993); Cox and Sumbler (2002); Palliani and Riding (2000); Slater et al (2015). Livera and Leeder 1981;Fisher and Hancock 1985;Kantorowicz 1985;Alexander 1989Alexander , 1992Riding and Wright 1989;Gowland and Riding 1991;Rawson and Wright 2000;Powell 2010).…”
Section: Geological Settingmentioning
confidence: 99%
“…1b). The Scalby Formation represents fluvio-deltaic conditions (Leeder and Nami 1979;Fisher and Milsom and Rawson (1989); Mjøs and Prestholm (1993); Palliani and Riding (2000); Rawson and Wright (2000). b Subdivision of the Middle Jurassic of Yorkshire.…”
Section: Geological Settingmentioning
confidence: 99%